International business : a managerial perspective - Griffin, Ricky W., 1950- (Pearson, 2020)
International Business illustrates how successful managers must function in a competitive world. Packed with current examples that showcase the vibrancy of international business, the text offers a managerial approach that emphasizes skills development, emerging markets, and geographical and cultural literacy. The 9th Edition features new cases, boxes and analyses reflecting the latest challenges and opportunities in the field. With this, you'll be prepared to effectively communicate with foreign business representatives and successfully conduct business with organizations worldwide.